The Effect of the Separation of Ownership from Control on Accounting Policy Decisions: A Comment. - Liao, Shu S. (The Accounting Review, 1979)
The purpose of this article is to discuss the inconsistency in findings reported, regarding the effect of separation of ownership from control on accounting policy decisions. The major surprise stressed in the study is that, when smoothing changed periods are compared with no-change periods, smoothing behavior takes place in both groups of firms when it has the most utility to management. When preliminary income is substantially different from the target, manager firms were expected to make smoothing changes. The main focus of these managerial theories generally has been determine what effect, if any, the type of control has upon the pattern in which managerial decisions are made. Modern managerial theories of the firm generally have criticized the neoclassical theories of managerial behavior for failing to maintain the distinction between owner-controlled firms and manager-controller firms and for testing hypotheses with samples drawn uncritically from populations which contain both owner-controlled firms and manager-controlled firms.